The Pathobiology of TDP-43 C-Terminal Fragments in ALS and FTLD - Berning, Britt A.; Walker, Adam K. (Frontiers in Neuroscience, 2019)
During neurodegenerative disease, the multifunctional RNA-binding protein TDP-43 undergoes a vast array of post-translational modifications, including phosphorylation, acetylation and cleavage. Many of these alterations may directly contribute to the pathogenesis of TDP-43 proteinopathies, which include most forms of amyotrophic lateral sclerosis (ALS) and approximately half of all frontotemporal dementia, pathologically identified as frontotemporal lobar degeneration (FTLD) with TDP-43 pathology. However, the relative contributions of the various TDP-43 post-translational modifications to disease remain unclear, and indeed some may be secondary epiphenomena rather than disease-causative. It is therefore critical to determine the involvement of each modification in disease processes to allow the design of targeted treatments. In particular, TDP-43 C-terminal fragments (CTFs) accumulate in the brains of ALS and FTLD patients and are therefore described as a neuropathological signature of these diseases. Remarkably, these TDP-43 CTFs are rarely observed in the spinal cord, even in ALS which involves dramatic degeneration of spinal motor neurons. Therefore, TDP-43 CTFs are not produced non-specifically in the course of all forms of TDP-43-related neurodegeneration, but rather variably arise due to additional factors influenced by regional heterogeneity in the central nervous system. In this review, we summarise how TDP-43 CTFs are generated and degraded by cells, and critique evidence from studies of TDP-43 CTF pathology in human disease tissues, as well as cell and animal models, to analyse the pathophysiological relevance of TDP-43 CTFs to ALS and FTLD. Numerous studies now indicate that, although TDP-43 CTFs are prevalent in ALS and FTLD brains, disease-related pathology is only variably reproduced in TDP-43 CTF cell culture models. Furthermore, TDP-43 CTF expression in both transgenic and viral-mediated in vivo models largely fails to induce motor or behavioural dysfunction reminiscent of human disease. We therefore conclude that although TDP-43 CTFs are a hallmark of TDP-43-related neurodegeneration in the brain, they are not a primary cause of ALS or FTLD.